Diminished ovarian reserve in girls and adolescents with Trisomy X Syndrome - Davis, Shanlee M (Reprod Sci, 2020)
An extra X chromosome occurs in ~1 in 1,000 females, resulting in a karyotype 47,XXX also known as trisomy X syndrome (TXS). Women with TXS appear to be at increased risk for premature ovarian insufficiency, however very little research on this relationship has been conducted. The objective of this case-control study is to compare ovarian function, as measured by anti-mullerian hormone (AMH) levels, between girls with TXS and controls. Serum AMH concentrations were compared between 15 females with TXS (median age 13.4 years) and 26 controls (median age 15.1 years). Females with TXS had significantly lower serum AMH compared to controls (0.7 ng/mL (IQR 0.2–1.7) vs 2.7 (IQR 1.3–4.8), p<0.001). Additionally, girls with TXS were much more likely to have an AMH below the 2.5(th) percentile for age with 67% of them meeting this criteria (OR 11, 95% CI 2.3–42). Lower AMH concentrations in females with TXS may represent an increased risk for primary ovarian insufficiency in these patients and potentially a narrow window of opportunity to pursue fertility preservation options. Additional research is needed to understand the natural history of low AMH concentrations and future risk of premature ovarian insufficiency in girls with TXS.